Torsional deviations with voluntary saccades caused by a unilateral midbrain lesion. Issue 10 (15th May 2007) - Kremmyda, Olympia; Büttner-Ennever, Jean A; Büttner, Ulrich; Glasauer, Stefan
Abstract : Three dimensional eye rotations were measured using the magnetic search coil technique in a patient with a lesion of the right rostral interstitial nucleus of the medial longitudinal fasciculus (RIMLF) and in four control subjects. Up to 10° contralesional torsional deviations with each voluntary saccade were revealed, which also could be seen during bedside examination. There was no spontaneous nystagmus. Based on MRI criteria, the lesion involved the RIMLF but spared the interstitial nucleus of Cajal. To date, this deficit has not been described in patients. Our results support the hypothesis that the vertical–torsional saccade generator in humans is organised similarly as in monkeys: each RIMLF encodes torsional saccades in one direction, while both participate in vertical saccades.